Indikator keberkesanan pendekatan pengurangan kemudaratan dan cabaran implementasi di peringkat agensi berkepentingan - Zakaria, Ezarina; Baba, Ismail; Azman, Azlinda (The Malaysian Journal of Social Administration, 2017)
Global efforts for the prevention of HIV / AIDS currently concentrate on intervention aimed at harm-reduction which comprises Needle and Syringe Exchance Program-NSEP This paper presents an analysis of previous studies on the effectiveness of harm-reduction. On the whole, NSEP intervention places emphasis on a major indicator, viz. a change from at-risk behaviour to not-at-risk behaviour and preventing the spread of HIV/ AIDS and other blood borne diseases. The paper confirmed about tbe importance of multisectorial involvement in promoting the effectiveness of NSEP. However, differences in interests, issue of acceptance and limitation on inter-agency involvement due to conformity to regulation and jurisdiction are identified as major challenges for implementing effective NSEP interventions.